Mobile E-Commerce UMKM Sumbawa - Muhammad Fauzi; Shinta Esabella (AMIK STIEKOM SUMATERA UTARA, 2023)
E-Commerce is an abbreviation of electronic commerce which means services related to the process of buying, selling and marketing products that are carried out digitally through electronic systems. At this time the Sumbawa Diskoperindag does not yet have an online shopping application for Sumbawa UMKM products, but only has a Sumbawa UMKM web portal application which is only an information medium related to typical Sumbawa souvenir products, so buyers cannot make shopping transactions. With this Mobile E-Commerce application, it is hoped that it will help Diskoperindag in promoting UMKM and Sumbawa typical souvenir products to all levels of society. This Mobile E-Commerce application was built using Android Studio, the Flutter framework and the Dart programming language using the extreme programming application development method. The Mobile E-Commerce application is built based on Android with a minimum Android 7.1.1 (Nougat) operating system. Application planning using object-based methods, namely User Modeling Language (UML) and application testing using the Black-box testing method. Based on the results of the tests carried out, it was found that the applications built went according to planning and development. The Mobile E-Commerce application can be uploaded and used on the Android 7.1.1 (Nougat) operating system. The result of this research is the creation of a prototype Android-based Sumbawa UMKM E-Commerce Mobile Application.